REPRESENTASI SOSOK IBU DALAM FILM KANGEN (Analisis Semiotika Roland Barthes Dalam Film Pendek) - Alva Jelang Ramadhani (2021)
Mother figure used in Indonesian film is just an ordinary thing. Mother figure represented as mom that love her children. But, in "Kangen" horror short film, mother figure that love her children is not present. This film have different way to the mother figure as film antagonist. Compared to popular Indonesian horror film, mother figure in "Kangen" film have unique trait. Mother figure in this film seen as a threat to her children while showing her affection. This research contains a review about a movie named "Kangen"as a result of collaboration between FIBER UPNVJ and Project Selasa.The purpose of this research is finding the representation of mother figure on this film. The object of the research is the scene of mother figure on "Kangen" film. This research using semiotic that assuming if investigating the sign that available on public or social phenomenon can reveal the meaning of the sign itself. The method in this study uses qualitative method with Roland Barthes semiotic analysis approach through denotation, connotation and myth.. The result of this research is that the representation of mother figure on "Kangen" short horror film show that every mother have a good side, but have a bad side too.